2008
DOI: 10.1021/ja8019005
|View full text |Cite
|
Sign up to set email alerts
|

Where Does the Electron Go? Electron Distribution and Reactivity of Peptide Cation Radicals Formed by Electron Transfer in the Gas phase

Abstract: We report the first detailed analysis at correlated levels of ab initio theory of experimentally studied peptide cations undergoing charge reduction by collisional electron transfer and competitive dissociations by loss of H atoms, ammonia, and N-C alpha bond cleavage in the gas phase. Doubly protonated Gly-Lys, (GK + 2H) (2+), and Lys-Lys, (KK + 2H) (2+), are each calculated to exist as two major conformers in the gas phase. Electron transfer to conformers with an extended lysine chain triggers highly exother… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(13 citation statements)
references
References 89 publications
(105 reference statements)
0
13
0
Order By: Relevance
“…[38] For example, ET,noD has been noted to be maximized when protonation takes place at a histidine residue, which has been attributed to the exothermic isomerization of the His (3H)-imidazoline radical to the more stable (2H)-imidazoline isomer under sterically favorable conditions. [61,62] For a given charge state, the histidine containing model peptides all show higher contributions from ET,noD than the peptide ions without histidine. Lysine was noted as giving rise to the least ET,noD and this is consistent with the near absence of the charge reduced electron transfer product for the triply protonated RGAGGKGAGGRL peptide.…”
Section: Resultsmentioning
confidence: 99%
“…[38] For example, ET,noD has been noted to be maximized when protonation takes place at a histidine residue, which has been attributed to the exothermic isomerization of the His (3H)-imidazoline radical to the more stable (2H)-imidazoline isomer under sterically favorable conditions. [61,62] For a given charge state, the histidine containing model peptides all show higher contributions from ET,noD than the peptide ions without histidine. Lysine was noted as giving rise to the least ET,noD and this is consistent with the near absence of the charge reduced electron transfer product for the triply protonated RGAGGKGAGGRL peptide.…”
Section: Resultsmentioning
confidence: 99%
“…ESI mass spectrum of the tetradecapeptide bombesin. 25 and is probably the one neutralized and transferred as a hydrogen atom to an uncharged amide oxygen (Cornell mechanism), 1 or the one migrating as a proton to a negatively charged (reduced) amide oxygen (Utah-Washington mechanism), 26,27 during the ETD process to form the observed sequence ions. In view of these facts, Arg is the most likely charge carrier in the final fragments.…”
Section: Resultsmentioning
confidence: 99%
“…The common feature of the valence excited states is that their energies form a very dense manifold containing many (10-15) electronic states within 1 eV of the ground electronic state. 45) The excited states differ in the electron and spin density distribution, which is mainly delocalized over π-electron "electrophores" such as peptide amide groups and side-chain imidazole and guanidine groups. Calculations on small peptide radicals indicated that these electrophores have very similar electron affinities (recombination energies, RE), typically ranging between 3.1-3.6 eV.…”
Section: Exd Mechanismsmentioning
confidence: 99%
“…Figure 5 shows two generic pathways that have been dubbed "egg" and "chicken" to depict the dilemma of deciding which of the following steps, proton transfer or bond dissociation, occurs first in the charge-reduced ion. 45) The "egg" pathway posits that the aminoketolate anion-radical first undergoes N-C α bond cleavage to form a complex of the incipient c and z fragments. The intermediate c fragment is formed as an imino enolate anion and must receive a proton to presumably form the more stable amide tautomer of the c type fragment with the experimentally observed elemental composition.…”
Section: Exd Mechanismsmentioning
confidence: 99%